People and politics: Urban climate resilience in Phnom Penh, Cambodia - Asif, Furqan; Beckwith, Laura; Ngin, Chanrith (Frontiers in Sustainable Cities, 2023)
The rapid growth Cambodia has experienced over the past two decades has resulted in a dramatic transformation of its built environment, in particular, its largest city, Phnom Penh. The shape this urban development has taken echoes that of many developing countries whose urban landscape features gleaming skyscrapers, apartment buildings, and edge-city projects spread across a rapidly expanding urban area. Such a pattern of urbanization is occurring in Phnom Penh while the city faces increased flooding, lack of adequate urban infrastructure, and vulnerability to impacts of climate change. At the same time, embedded within national policy discourses of climate change and social/economic planning, and backed by international donors, are calls for strengthening or developing resilience. Yet, in the city there are signs of land dispossession, marginalization, inequality, and exacerbated poverty. In parallel to high-level discourses of urban resilience, on the ground there have been “everyday forms of resilience” that show how people enact and build resilience through collective action and advocacy for the rights of the urban poor. In reconciling this dichotomy, we argue that the continued reproduction of a technocratic-focused discourse on resilience in Cambodia by national and international actors overshadows the everyday contestations, strategies and resilience-making practices of people in urban areas. Through three examples, we showcase the varying ways in which these contestations and strategies occur in, and despite, an environment of suppression, and how they are challenging the status quo. In doing so, we shed light not only on the politics of resilience but, more importantly, the implications of the political agendas that ultimately contribute to exacerbating vulnerabilities of urban residents, even as calls continue for increased urban “resilience.”